ANALYSIS OF STUDENTS' DIFFICULTIES IN LEARNING MATHEMATICS OF CIRCLE GEOMETRY IN FOURTH GRADE ELEMENTARY SCHOOL - Aeunah, Een; Aziz, Abdul; Joe, Caecilia Jilia; Ali, Cut Dihe Zayhaqqi (Transpublika Publisher, 2023)
The present study endeavors to comprehensively examine the obstacles faced by elementary school students when attempting to grasp fundamental mathematical concepts pertaining to circles. Specifically focusing on Grade 4 students at SDN Cipondoh 2, Tangerang City. The primary objective is to shed light on the difficulties encountered by students in three core areas: calculating circle area and circumference, understanding the complex concept of π (pi), and accurately sketching circles utilizing a compass. Various tools are employed to scrutinize the obstacles students encounter, including tasks such as calculating circle area and circumference, comprehending the intricate π (pi) concept, and accurately sketching circles using a compass. The findings indicate that students encounter hurdles in computing circle area and circumference due to the need to understand underlying formulas and calculation procedures. Additionally, comprehending the π (pi) concept presents a notable challenge in circle calculations. Moreover, students struggle with precise and symmetrical circle drawing using a compass. The research outcomes provide valuable insights for formulating effective pedagogical strategies to help students overcome challenges in comprehending and applying circle geometry principles.